Identification and characterisation of an extrachromosomal element from a multidrug-resistant isolate of trypanosoma brucei brucei. - Jamnadass, Ramni H. (Brunel University, 1995)
Drug resistance together with difficulties involved in the development of new trypanocides are a major problem in the present control of African trypanosomiasis. DNA based diagnostics for drug resistance would overcome problems in the identification of drug-resistant populations and contribute to effective control measures. However, this requires a detailed knowledge of the mode of action and the mechanisms by which trypanosomes can overcome the toxic effects of trypanocides. In this study, a search for molecular differences between a multidrug-resistant isolate of Trypanosoma brucei brucei, CP 547, and a reference drug-sensitive population, ILTat 1.4, led to the identification of a 6.6 kbp extrachromosomal element in the multidrug-resistant population. In light of the involvement of extrachromosomal elements in drug resistance in Leishmana spp. and cancer cells, the identification of the 6.6 kbp element warranted its characterisation. Several different approaches sere attempted before a sequence which hybridised to the 6.6 kbp element its eventually isolated. This sequence is represented by a 108 bp repeat sequence which forms long arrays of tandem repeats. Since N/a III is the sole restriction enzyme that cuts within the repeat, it has been referred to as an N/a III repeal The repeat is flanked by a 5 bp spacer sequence. However, a unique 5 bp direct repeat flanking two complete, and one partial copy of the N/a III repeat may signify the transposition of these sequences. Hybridisation with the N/a III repeat revealed the presence of 'higher' hybridising elements which also appear to be predominantly composed of long tandem arrays of the N/a Ill repeal Through exploitation of the p01) merase chain reaction using arbitrary primers (AP-PCR), additional sequences were identified which are associated with some of the 6.6 kbp and 'higher' hybridising elements. The 6.6 kbp element and some of the 'higher' hybridising elements display features of circular DNA molecules. The 6.6 kbp element also displays some level of size and sequence heterogeneity within different populations of the same trypanosome isolate. The copy number of the 6.6 kbp element is also not stable and appears to be directly affected by the application of selective drug pressure, but a direct association between the presence of the element and the expression of multidrug resistance could not be determined. The N/a III repeat family represents a newly identified repetitive family specific to members of the Trypanozoon subgenus. This repeat family, representing about 5% of the parasite genome, is dispersed through all size classes of chromosomes, in addition to its presence on the extrachromosomal elements. Transcriptional studies of the N/a III repeats have revealed that their transcription is developmentally regulated, since heterogeneous transcripts ranging from greater than 10 kb to smaller than 300 bp are present in the actively dividing long slender bloodstream and insect stage procyclic forms of the parasite but not nondividing, stumpy bloodstream forms. Lastly, the N/a III repeat lacks an open reading frame and transcripts do not appear to have a spliced leader sequence at the 5' end. Furthermore, there is almost an equal representation of polyadenylatcd and non-polyadenlyated transcripts.